LEGAL NATURE AND MAIN PROCEDURAL DETERMINANTS OF CRIMINAL PROCEDURE IN BOSNIA AND HERZEGOVINA - Sadmir Karović; Marina M. Simović (Revija za kriminologiju i krivično pravo)
In this paper, the authors analyse the legal nature of criminal procedure in Bosnia and Herzegovina, with the special emphasis on reform processes of criminal procedure legislation and adoption and acceptance of new legal solutions over the past two decades, acknowledging the aspiration for effectiveness and protection of basic human rights and freedoms. For the purpose of effective criminal procedure, it identifies the main and secondary actors in criminal proceedings whose role is crucial from the aspect of shedding light on and resolving a certain criminal matter, as well as issuing a judicial decision. To that end, the role and importance of those actors in taking procedural actions to carry out a criminal procedure task is emphasised for the purpose of understanding the legal nature, structure and course of the criminal procedure, and achieving the scope of legally prescribed rights of the suspect, that is, the defendant. In addition, special attention is paid to the specific procedural situation and status of an underage person in the criminal law as the perpetrator and injured parties in a criminal case, taking into account their age as the basis for the differentiation and protection in relation to adults.